Does money "buy" tolerance toward damage‐causing wildlife?. Issue 3 (30th August 2020) - Kansky, Ruth; Kidd, Martin; Fischer, Joern
Abstract: The Kavango‐Zambezi Transfrontier Conservation Area supports large‐scale migrations of wildlife that occur in a mixed agri‐conservation landscape in five Southern African countries. Human–Wildlife Conflict is a key challenge and understanding the drivers of communities' willingness to coexist with wildlife is thus critical. Community based natural resource management (CBNRM) is a widely used economic approach to foster human‐wildlife coexistence with the assumption that monetary benefits can "buy" tolerance by offsetting the disservices of living with wildlife. We tested this assumption and hypothesized that Namibians would be more tolerant towards wildlife than Zambians because they received higher monetary benefits from wildlife. We used the Wildlife Tolerance Model (WTM) as the framework to define tolerance and identify tolerance drivers. We found Namibians tolerance was higher for lion, elephant and hyena but not for kudu and baboon. After controlling for confounding variables of the WTM that could potentially explain differences in tolerance, contrary to expectation, the monetary benefits did not account for higher Namibian tolerance. Instead, only nonmonetary benefits explained the higher tolerance. We used crowding theory to explain this finding, proposing that CBNRM in Namibia and the monetary benefits from the program "crowd in" intrinsic motivation to appreciate and tolerate wildlife. Abstract : Living with elephants near Sangwali village in Wuparu conservancy, Namibia